Pengembangan Website Toko Online Baju Bekas (Studi Kasus : Toko Gudang Jumat) - Bagas Rayi Prabowo; Issa Arwani; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Toko Gudang Jum'at is a place to sell used clothes or more commonly known as a thrift shop. Currently, the Toko Gudang Jum'at does not have a physical store and only promotes its sales through Instagram social media. To assist the transaction process and also the promotion of Toko Gudang Jum'at itself, an online store website was developed that can assist in the transaction process and promotion. The website development carried out is expected to help customers to be able to recognize and make transactions with Toko Gudang Jum'at. The development of the admin dashboard system will also be carried out to make it easier for Toko Gudang Jum'at to manage the products they sold and monitor order reports and also transactions on the Toko Gudang Jum'at website. System development will start from the needs analysis process carried out using the interview method with Toko Gudang Jum'at, followed by the design stage to design the system in the form of diagrams such as class diagrams, sequence diagrams, and physical data modeling. Implementation is done by creating a website using the Laravel framework for the backend or dashboard admin page and Vue JS for the frontend or customer page. The two systems will be connected by a RESTful Web Service for the data exchange process. The results of the system implementation were tested with 3 types of tests, namely, REST API testing using the Postman application, black box testing, and usability testing using a usability testing system which was carried out on 5 respondents. The results of black box testing for all functional indicate valid status. Usability testing using the usability testing system shows an average rating of 77.5. According to the general guidelines on the interpretation of the SUS score, the score is grade B, which means the system can be used properly.